Pengaruh Metode Drill Terhadap Peningkatan Keterampilan Servis Panjang Bulu Tangkis Pada Atlet Superdan Badminton Academy - Fadri, Kurniadi; Banat, Azizatul; Utama, Eko Putra (UNIVED Press, Universitas Dehasen Bengkulu, 2025)
This research investigates the effectiveness of drill method in improving long service skills among badminton athletes at Superdan Badminton Academy, Bengkulu City, employing a quantitative experimental approach with pretest-posttest design involving 10 athletes who underwent structured drill training for six weeks. Long service technique represents a fundamental skill in badminton that requires precise coordination, strength, and accuracy to direct the shuttlecock to the opponent's backcourt area, creating defensive pressure and strategic advantages, while the drill method was selected due to its systematic approach emphasizing repetitive movements, progressive skill development, and muscle memory formation through consistent practice patterns. Data collection utilized long service tests with 10-20 shuttlecocks per session across 16 training meetings, measuring accuracy, power, and consistency parameters, with statistical analysis revealing significant improvement from pretest mean score of 29.6 to posttest mean score of 35.7, representing a substantial increase of 6.1 points. The paired t-test demonstrated statistical significance with t-calculated (8.71) exceeding t-table (1.833) at 95% confidence level, confirming the drill method's effectiveness, while frequency distribution analysis showed positive shifts in skill categories, with no athletes remaining in the poor category post-treatment, 50% achieving good category and 50% maintaining adequate category performance. The research concludes that drill method significantly enhances long service skills through structured repetition, progressive training intensity, and systematic skill development, providing empirical evidence for coaches to implement drill-based training programs as an efficient strategy for technical skill improvement in badminton, particularly beneficial for academies with limited training time and facility constraints.